O ensino do empreendedorismo na educação formal de crianças: um estudo de caso na rede municipal de Itaperuçu - Garcia, Antonio Celso Rezende (2015)
The aim of this work is to analyze the discourse about entrepreneurship presented to children of the fifth year of municipal schools in Itaperuçu / PR. The research was developed from the perspective of Critical Organization Studies. As a method, we used the qualitative approach of a case study with data collection at a school belonging to the municipal net of Itaperuçu, from observation as well as interviews with the Secretary of Education, the responsible for methodology of teaching entrepreneurship, the teacher and two children. The data were organized from maps of ideas association, for their examination, followed the precepts of discourse analysis which allowed to investigate the ideological discourse of entrepreneurship presented for children. These results evoke reflections about the role of entrepreneurship education for children enrolled in the early grades of formal education.